Impact on the family of a child’s rare disease: A large cross-sectional study - Judith M. Jobling; Suzy M. Teutsch; Guy D. Eslick; Elizabeth J. Elliott (Rare)
Introduction: Children living with rare diseases (RD) require considerable support from their families. Aim: To assess the impact of children’s RD on family functioning and evaluate predictors of the level of impact. Methods: Families of Australian children aged < 19 years and living with a RD were invited to complete a comprehensive survey. Impact on family (IOF) score, using the validated IOF scale, embedded within the survey, was used as the main outcome measure. Results: Families of 462 children with > 240 different RD completed the survey. IOF scores increased as child health functioning (HF) worsened (Odds ratio [OR]= 97.3 [95 % CI 40.6–233.4] for severely reduced compared to excellent HF). Speaking a first language other than English (OR 2.9; 95 % CI 1.4–6.3), experiencing financial difficulty (OR 2.9; 95 % CI 1.4–3.1), long wait times to see a specialist doctor (OR 1.9; 95 % CI 1.3–2.9), and having two versus one child with a RD (OR 3.8; 95 % CI 1.1–14.5) were also associated with higher IOF scores. Conversely, IOF scores significantly decreased as the age of children increased (6–11 y: OR 0.6 (95 % CI 0.4–0.9); 12–18 y: OR 0.5 (95 % CI 0.3–0.8), versus 0–5 y). Conclusion: Worse health-related functioning in children with RD results in significantly higher impacts on family functioning. Practical, financial, and socio-emotional support is required to reduce the burden for families whose children live with a RD, particularly families from non-English speaking backgrounds, with financial stress, or with young children who have severe disease.